Study to compare the morbidity of acute respiratory tract infections among children in an Urban and a Rural Community - Ariyaratne, A.K.S.K (My University, 1990)
A cross sectional study was carried-out to determine and compare the incidence and the treatment pattern of ARI among children of 0-4 year age group. Mild ARI were the commonest clinical entity encountered in both the communities, accounting to 69.8 per cent in the urban area and 77.4 per cent in the rural area. The existing knowledge, attitudes and practices of mothers regarding ARI were satisfactory and encouraging. However, in the treatment of mild, moderate and severe forms, a certain proportion of mothers neither practiced any treatment nor aware of the measure to be taken. A certain level of domestic air pollution would have contributed to the incidence of ARI, although the causes appeared to be different